Effect of hemodialysis on the hearing function of patients with chronic renal failure (2006)
Sensorineural hearing impairment (SHI) has been reported in chronic renal failure (CRF) patients with a prevalence of 20-40%. The aetiopathogenetic mechanisms reported included osmotic alteration resulting in loss of hair cells and in some, complications of haemodialysis have been hypothesized' We have in the past reported 2 cases of CRF patients who developed acute SHL following hemodialysis. This is a report of investigation of the effect of hemodialysis on the hearing function of CRF patients using pure tone audiometry findings. Thirty-three CRF patients were recruited for Pure Tone Audiometry (PTA) at admission and after three sessions of hemodialysis. The pure tone audiometry was done with a computer audiometer BA 20 Kamplex in the sound - proof (acoustic) booth in the ENT clinic. The duration of illness, dosage of diuretics and blood pressure were also noted. Similar age and sex-matched control were selected among volunteers who were otherwise clinically healthy. The data was processed using the Statistical Package for the Social Sciences (SPSS Inc, Chicago, Illinois, USA). Thirty-three CRF patients treated with haemodialysis and 28 healthy controls completed the study, 34 males and 27 females, age range was 16 - 72 years, mean of 45.30 (SDI6.20) for subjects and 49.7 for controls. Hearing loss was found in 22/34 (67%) at recruitment and 27/34 (79%) after 3 sessions of hemodialysis. There was a significant difference between the mean pre- and post-hemodialysis PT A values, P =0.0008. There was also a signiticant correlation between post-hemodialysis hearing threshold and (i) duration of illness (P = 0.00340) and (ii) creatinine levels of the patients (P=0.035). In conclusion, there was a significant depression in the hearing threshold of patients with CRF following three sessions of hemodialysis. This could be caused by changes induced by hemodialysis or effects of the duration and severity of disease.